Comparative Analysis of Cellular Phenotypes Within the Neointima From Vein Segments Collected Prior to Vascular Access Surgery and Stenotic Arteriovenous Dialysis Accesses. Issue 3 (17th December 2013) - Lee, Timmy; Wang, Yang; Arend, Lois; Cornea, Virgilius; Campos, Begona; Munda, Rino; Roy‐Chaudhury, Prabir
Abstract Venous stenosis, secondary to venous neointimal hyperplasia (VNH), at the arteriovenous anastomosis (AV) is a major etiology of vascular access failure in AV fistulas (AVF) and AV grafts (AVG). Recently, our group has reported that severe VNH also occurs prior to vascular access placement. The objective of this study was to perform a comparison of the cellular phenotypes within the neointima from veins collected from subjects at the time of new vascular access creation and stenotic veins from subjects with failed AVGs and AVFs. Vein samples, collected at the time of new access surgery, and stenotic vein segments, collected at access revision, were evaluated for expression of α‐smooth muscle actin (SMA), vimentin, and desmin within the neointima, and quantified using semiquantitative scoring. Within the neointima, the majority of cells from vein samples collected at the time of new access surgery were contractile smooth muscle cells, and veins from stenotic AVF and AVG were predominately myofibroblasts. Our results suggest the possibility of different mechanistic pathways in response to vascular injury that occurs prior to vascular access creation vs. after access creation, and that divergent therapeutic approaches may be needed for treating vascular injury in these two settings.